Improving the Concept Understanding and Scientific Attitudes through the Implementation of Scientific Approach - Zahara, Syarifah; Haji, Abdul Gani; Syukri, Muhammad (Universitas Islam Negeri Raden Intan Lampung, 2018)
This study aims to determine the improvement of conceptual understanding and scientific attitude of students through the application of scientific approach in junior high school. This research uses the quasi-experiment method with non-equivalent control group design. This research of scientific approach to science learning has been done in SMPN 1 Teunom and Pasie Raya. The population of this study was all students in both schools and class VIIA and VIIB was selected as the samples through purposive sampling. The data of this study were collected by using multiple choice test and observation sheet of students' scientific attitude. Data were analyzed using N-gain test and t-test after normality and homogeneity test were conducted using the SPSS program. The results showed that the application of scientific approach can improve the understanding of the concept and scientific attitude of the students with a value of t 0,000 < 0.05. The result of scientific attitudes obtained 76 and 70 % within the good category. This study concluded that an effective scientific approach can be used to improve understanding of students' concepts and scientific attitudes.